Analgesic Activity Test of Carrot (Daucus carota L.) Peel Extract on White Mice - Lintang Kumala Rahayu; Ratih Arum Astuti; Angga Bayu Budiyanto (Sean Institute, 2025)
Pain is an unpleasant experience characterized by potential tissue damage. One plant that has the potential to inhibit pain through its chemical compounds, namely flavonoids and alkaloids, is carrot peel (Daucus carota L.). The purpose of this study was to determine the analgesic activity of carrot peel extract in male mice. Carrot peel was extracted using the maceration method with 96% solvent. This study used 15 mice as test animals, which were divided into 5 treatment groups, namely the negative control group (CMC-Na), the positive control group (Sodium Diclofenac), carrot peel extract 100 mg/kgBW, 150 mg/kgBW, and 200 mg/kgBW. The test was conducted using the tail flick method with an analgesia measuring device. The test was conducted using the tail flick method with an analgesia measuring device. The data obtained were then analyzed using a paired sample t-test. The results showed that the three doses of carrot peel ethanol extract, 100 mg/kgBW, 150 mg/kgBW, and 200 mg/kgBW, did not have analgesic activity in male mice.